On properties of subdifferential mappings in Fréchet spaces - Kasyanov, P. O.; Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We present conditions under which the subdifferential of a proper convex lower-semicontinuous functional in a Fréchet space is a bounded upper-semicontinuous mapping. The theorem on the boundedness of a subdifferential is also new for Banach spaces. We prove a generalized Weierstrass theorem in Fréchet spaces and study a variational inequality with a set-valued mapping.